Building a sustainable school-wide adolescent literacy model in middle schools: Guidance for administrators. Issue 3 (27th May 2019) - Wexler, Jade; Swanson, Elizabeth; Vaughn, Sharon; Shelton, Alexandra; Kurz, Leigh Ann
Abstract: It is essential for middle school leaders to develop and promote school-wide literacy models, organizational structures that have a significant impact on the learning environment for all students in their building. However, school-wide literacy models can be difficult to implement and sustain over time. Drawing from an Office of Special Education Programs (OSEP) funded model demonstration project, PACT Plus, we provide a set of action steps for committed leaders to consider when initially adopting practices for a school-wide literacy model and to help leaders create a shared vision that promotes the implementation and sustainability of practices over time. In this article, we review the importance of using students' data to choose evidence-based literacy practices. We also provide guidance on how middle school leaders can encourage the adoption and use of these practices, so teachers implement the practices with high levels of fidelity of implementation.